Metabolic cooperativity between Porphyromonas gingivalis and Treponema denticola. Issue 1 (1st January 2020) - Kin, Lin Xin; Butler, Catherine A.; Slakeski, Nada; Hoffmann, Brigitte; Dashper, Stuart G.; Reynolds, Eric C.
ABSTRACT: Background:   Porphyromonas gingivalis  and  Treponema denticola  are proteolytic periodontopathogens that co-localize in polymicrobial subgingival plaque biofilms, display  in vitro  growth symbiosis and synergistic virulence in animal models of disease. These symbioses are underpinned by a range of metabolic interactions including cooperative hydrolysis of glycine-containing peptides to produce free glycine, which  T. denticola  uses as a major energy and carbon source. Objective:  To characterize the  P. gingivalis  gene products essential for these interactions. Methods: The  P. gingivalis  transcriptome exposed to cell-free  T. denticola  conditioned medium was determined using RNA-seq.  P. gingivalis  proteases potentially involved in hydrolysis of glycine-containing peptides were identified using a bioinformatics approach. Results:  One hundred and thirty-twogenes displayed differential expression, with the pattern of gene expression consistent with succinate cross-feeding from  T. denticola  to  P. gingivalis  and metabolic shifts in the  P. gingivalis  folate-mediated one carbon superpathway. Interestingly, no  P. gingivalis  proteases were significantly up-regulated. Three  P. gingivalis  proteases were identified as candidates and inactivated to determine their role in the release of free glycine.  P. gingivalis  PG0753 and PG1788 but not PG1605 are involved in the hydrolysis of glycine-containing peptides, making free glycine available for  T. denticola  utilization. Conclusion:  Collectively these metabolic interactions help to partition resources and engage synergistic interactions between these two species.